QlikView Your Business : An expert guide to Business Discovery with QlikView and Qlik Sense /: An expert guide to Business Discovery with QlikView and Qlik Sense. ([2015]) - Troyansky, Oleg; Gibson, Tammy; Leichtweis, Charlie
No abstract available